INOVASI KULIT KUE DADAR GULUNG SEBAGAI CAMILAN KHAS KOTA BANDUNG DENGAN MENGGUNAKAN UBI JALAR UNGU DAN UBI JALAR CILEMBU - Artin Bayu Mukti; Azis Nur Rosyid; Ndaru Prasastono (Kepariwisataan: Jurnal Ilmiah, 2022)
This research was conducted with the aim of making an innovation of rolled omelet skin and testing the use of purple sweet potato and cilembu sweet potato as ingredients for the rolled pancake skin. The method used in this research is descriptive, with the respondents being people who are willing to try and give an assessment of the results of the roll omelet skin innovation. Data collection methods used are respondents, questionnaires, sensory tests, and literature study. The results of data analysis and discussion used in this study are quantitative data analysis with a total of 110 respondents. The assessment criteria include texture, color, aroma, and taste. Meanwhile, the conclusion of this research is that the average sensory test value is mostly found in purple sweet potato, which is 4,309 for the taste indicator and the average sensory test value for the Cilembu sweet potato is the most common in the taste indicator, which is 4,473. Furthermore, from the observations of the researchers, there were samples and the average sensory test samples for the assessment of texture, aroma, colour, and taste, respondents were more dominant with rolled omelet using sweet potato cilembu.Keywords: Purple Sweet Potatoes, Cilembu Sweet Potatoes, Rolls Omelet Skin, and Snacks.